(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
In this paper, we document the experienced synthesis of graphene quantum dots (GQDs) from coconut husk, normal biomass as a biosynthesis precursor utilizing a single-step hydrothermal carbonization. Structural and morphological characterization of these GQDs was carried out using XRD, Raman, and FTIR. As synthesized at the same time, XRD results established their crystalline nature. Raman spectroscopic measurements exhibited the characteristic "D" (a thousand cm⁻¹) and "G" (3500 cm⁻¹) bands, confirming the formation of low-dimensional graphene nanostructures. Optical properties of these GQDs had been probed, making use of UV-seen spectrometry and room temperature photoluminescence measurements. The UV-vis spectrum confirmed a powerful absorption at 320 nm. These GQDs exhibited fluorescence regularly at 440 nm when excited at one-of-a-kind wavelengths. The fluorescence of GQDs was observed to be sensitive to pH linearly over the pH range of four to 12, which may also be exploited for pH sensor purposes. FTIR spectroscopy has proven the presence of hydroxyl and carboxyl practical moieties on the surface of the GQDs, which play a significant position in surface passivation leading to extra steady nanoparticle dispersions. Coconut husk extract-Graphene quantum dots confirmed the greatest antimicrobial undertaking towards several bacteria species akin to Pseudomonas aeruginosa, Streptococcus mutans, Streptococcus aureus, & E. coli. Established on the findings of the learn, coconut husk might be exploited in developing talents in bioactive pharmaceutical medicines for mighty therapy of cancer.